The effect of UDMA and Bis-GMA irradiation period on residual monomers in resin packable composite - Jayanti Rosha; Adioro Soetojo; Putu Dewi Purnama Sari Budha; M. Mudjiono (Dental Journal (Majalah Kedokteran Gigi), 2019)
Background: Residual monomers are non-polymerized monomers which can cause clinical harm, for example inflammation, to oral cavity tissue while the remaining monomers can potentially be carcinogenic. The more residual monomers that remain due to an imperfect polymerization processes, the lower the compressive strength level and the higher the number of micro slits that can cause secondary caries and tooth sensitivity. Urethane dimethacrylate (UDMA) and bisphenol A glycol dimethacrylate (Bis-GMA) constitute two of the resins most frequently used in packable composites. During the short irradiaton period forming part of the polymerization process, UDMA and Bis-GMA have the potential to produce residual monomers. Purpose: This study aimed to compare the number of residual monomers in packable composite resin following irradiation lasting 1x20 seconds and 2x20 seconds. Methods: 28 samples of cylindrical packable composite with a thickness of 2 mm and a diameter of 5 mm were divided into four groups. Groups 1 and 2 were irradiated for 1x20 seconds, and groups 3 and 4 for 2x20 seconds with the composite subsequently being immersed in ethanol solution for 24 hours. The number of residual monomers using high-performance liquid chromatography (HPLC) devices was calculated and the results statistically analyzed using a Mann-Whitney Test. Results: Repeated irradiation had no effect on the amount of residual monomers in packable composite resins. However, there were differences in the number of residual monomers in the material contained in packable composite resins Bis-GMA and UDMA, while the remaining monomers in UDMA outnumbered those in Bis-GMA. Conclusion: The number of residual monomers in Bis-GMA is lower than in the remaining UDMA after 1x20 seconds irradiation, while the number of residual monomers in Bis-GMA and UDMA following 2x20 seconds irradiation was no different to that after irradiation of 1x20 seconds duration.